Comparative performance analysis of a turboprop engine used in regional aircraft by considering design and flight conditions - Yuksel, Onur; Aygun, Hakan (Emerald Group Publishing Ltd, 2025)
PurposeThis study aims to evaluate variation of performance metrics involving specific fuel consumption (SFC), thrust, thermal efficiency and overall efficiency values of turboprop engine used in regional aircraft according to varying altitude of 0-9 km and 0.3-0.6 Mach ranges. Moreover, influences of design parameters such as overall pressure ratio (OPR) ranging between 12 and 15 and turbine inlet temperature (TIT) ranging between 1,200 K and 1,400 K regarding the engine are dealt with by using ideal and real codes of parametric cycle equations.Design/methodology/approachThis study is performed based on thermodynamic analysis for real and ideal conditions by means of MATLAB software.FindingsWhen considering influences of flight conditions, SFC of the PW127-E changes between 6.4 g/kNs and 13.75 g/kNs at ideal conditon whereas changes between 6.9 g/kNs and 14.64 g/kNs at real conditions. Moreover, overall efficiency of the engine varies between 28.3% and 35.5% at ideal, whereas it is found between 12.8% and 18.5% at real condition owing to varying altitude and Mach. On the other hand, with effects of design variables, SFC of the engine changes between 9.59 g/kNs and 10.38 g/kNs at ideal however 11.74 g/kNs and 12.76 g/kNs at real. Lastly, overall efficiency of the engine resides between 30.61% and 33.13% at ideal whereas between 14.37% and 18.61% at real due to varying OPR and TIT variables.Practical implicationsIt is expected that this study helps in understanding how to vary performance metrics of the engine according to internal variables and external conditions. Namely, the approach used in present study could benefit the determination of the on-design and off-design performance of the engine in theoretical manner.Originality/valueThe novelty of this study is to present performance analysis of the three-shaft PW127-E turboprop by considering the effect of design parameters and flight conditions on engine performance in ideal and real conditions.
Keywords: Turboprop; Parametric cycle analysis; Efficiency; Regional aircraft